Pengaruh Pengalaman Kerja, Kompetensi dan Independensi terhadap Kualitas Audit: Studi Kasus pada Kantor Inspektorat Daerah Kabupaten Se-provinsi Gorontalo - Djafar, Gustin; Blongkod, Harun; Usman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The results of this research show that (1) Work experience does not have a positive and significant effect on audit quality in district inspectorate offices in Gorontalo province. if the t-value or C.R is 0.551 < 1.660 or the P value is 0.582 > 0.05 then H1 is rejected, so it can be concluded that work experience has no positive and significant effect on audit quality in regional inspectorates in districts throughout Gorontalo Province. (2) Competence has a positive and significant effect on audit quality in district inspectorates throughout Gorontalo province. if the tvalue or C.R variable is 1.694 > 1.660 or the P value is 0.09 <0.05, then H2 is accepted, so it can be concluded that competency has an influence on audit quality in district inspectorates throughout Gorontalo Province. This shows that the better the competency, the better the quality of the audit that will be received. (3) Independence has a positive and significant effect on the quality of audits in district inspectorates throughout Gorontalo province. if the tvalue or C.R variable is 4.334 > 1.660 or the P value is *** < 0.05, then H2 is accepted, so it can be concluded that competency has an influence on audit quality in district inspectorates throughout Gorontalo Province. This shows that the better the competency, the better the audit quality that will be received. (4) Work experience, competence and independence have a positive and significant effect on audit quality at district regional inspectorate offices throughout Gorontalo province. The R-square value of the oxygen latent variable for the audit quality latent variable is 0.858 or 85.8%. meaning, the endogenous latent variable is simultaneously influenced or can be explained by the exogenous latent variable work experience, competence and independence by 85.8%. Meanwhile, the remaining 14.2% is explained by other variables outside the research model. Thus, it can be concluded that work experience, competence and independence simultaneously have a positive and significant effect on audit quality in regional inspectorate offices in the districts of Gorontalo Province.